Intercellular mitochondrial transfer: bioenergetic crosstalk between cells. (June 2016) - Sinha, Pratik; Islam, Mohammad N; Bhattacharya, Sunita; Bhattacharya, Jahar
Abstract : Mitochondrial transfer from donor cells to cells of injured tissues is a promising cell-based therapy for effectively bringing about recovery of tissue bioenergetics. Here, we review recent studies on intercellular mitochondrial transfer in organs and cells. We also review studies that shed light on our current understanding of the known mechanisms and conditions that lead to intercellular mitochondrial transfer.